Newborn behavioral observations system in rural Pakistan: A feasibility and acceptability study. Issue 1 (15th December 2022) - Parveen, Shazia; Zeshan, Muhammad; Naveed, Sadiq; Levey, Elizabeth; Jahan, Nusrat; Harrison, Alexandra Murray
Abstract: The Newborn Behavioral Observations (NBO) system is a relationship‐based tool that helps parents recognize their infant's competencies and learn their behavioral cues, with the goals of enhancing parental responsiveness and satisfaction in the infant‐parent relationship. In our study, a pediatrician integrated the NBO into 44 pediatric health care visits of infants in rural Pakistan villages, under the remote guidance of two U.S.‐based child psychiatrists. A clinician then gave the mothers a survey about their experience of the NBO and found that the mothers were highly satisfied, reporting greater appreciation of their infant's strengths, greater understanding of their infant's behavioral cues, stronger attachment to their infant, and greater self‐confidence as a mother. In their consideration of these results, the authors explore cultural reasons for the mothers' responses and generate hypotheses to inform an outcome study of a similar intervention. This was a feasibility and acceptability study and was not randomized, had no control group, and did not use objective measures of outcome. Resumen: El sistema de Observaciones de Comportamiento del Recién Nacido (NBO)™ es una herramienta basada en la relación que se enfoca en ayudar a los padres a reconocer las competencias de su infante y aprender sus señales de comportamiento, con el propósito de mejorar la sensibilidad y satisfacción del progenitor en la relación infante‐progenitor. En este estudio de probabilidad y aceptabilidad, un clínico pediatra integró el NBO dentro de 44 visitas de cuidado de salud pediátricas a infantes en aldeas rurales en Pakistán, bajo la guía remota de dos siquiatras infantiles con base en los Estados Unidos. Entonces, un clínico les dio a las madres una encuesta acerca de su experiencia con el NBO y se encontró que las madres estaban altamente satisfechas, reportando un mayor aprecio por los puntos fuertes de sus infantes, una mayor comprensión de las señalas de comportamiento de sus infantes, una más fuerte afectividad hacia sus infantes, así como una mayor auto confianza como madre. En sus consideraciones de estos resultados, los autores exploran razones culturales para las respuestas de las madres y generan hipótesis como información para un estudio de resultado de una intervención similar. Résumé: Le système d'observation comportementale du nouveau‐né (Newborn Behavioral Observations, abrégé selon l'anglais NBO system™) est un outil basé sur la relation se concentrant sur l'aide aux parents à reconnaître les compétences de leur nourrisson et à comprendre leurs signaux de comportement, se donnant pour but de mettre en valeur la réaction parentale et la satisfaction dans la relation nourrisson‐parent. Dans cette étude de faisabilité et d'acceptabilité un clinicien en pédiatrie a intégré le NBO dans 44 visites de santé pédiatrique de nourrissons dans des villages du Pakistan rural, sous l'orientation professionnelle à distance de deux psychiatres de l'enfance basés aux Etats‐Unis d'Amérique. Un clinicien a ensuite donné aux mères un questionnaires sur leur expérience du NBO et a trouvé que les mères étaient très satisfaites, faisant état d'une plus grande appréciation des forces de leurs nourrissons, d'une plus grande compréhension des signaux de comportement de leur nourrisson, d'un attachement plus fort à leur nourrisson et d'une plus grande confiance en soi en tant que mère. Dans leur considération de ces résultats les auteurs explorent les raisons culturelles expliquant les réponses des mères et génèrent des hypothèses pour informer une étude d'une intervention similaire. Zusammenfassung: System zur Verhaltensbeobachtung von Neugeborenen im ländlichen Pakistan: Eine Machbarkeits‐ und Akzeptanzstudie Das System zur Verhaltensbeobachtung von Neugeborenen (Newborn Behavioral Observations; NBO‐System™) ist ein beziehungsorientiertes Instrument, das Eltern helfen soll, die Kompetenzen ihres Säuglings zu erkennen und dessen Verhaltenshinweise zu deuten. Ziel des Beobachtungsinstruments ist es, die elterliche Reaktionsfähigkeit und die Zufriedenheit in der Eltern‐Säuglings‐Beziehung zu verbessern. In dieser Machbarkeits‐ und Akzeptanzstudie integrierte ein:e Pädiater:in die NBO unter der Anleitung zweier Kinderpsychiater:innen aus den USA in 44 pädiatrische Gesundheitsversorgungsbesuche von Säuglingen in Dörfern im ländlichen Pakistan. Ein:e Mediziner:in befragte im Anschluss die Mütter zu ihren Erfahrungen mit der NBO und stellte fest, dass die Mütter sehr zufrieden waren. Sie berichteten von einer größeren Wertschätzung der Stärken ihres Säuglings, einem besseren Verständnis der Verhaltenshinweisen ihres Säuglings, einer stärkeren Bindung zu ihrem Säugling und einem größeren Selbstvertrauen als Mutter. In ihren Überlegungen zu diesen Ergebnissen untersuchen die Autor:innen kulturelle Gründe für die Reaktionen der Mütter und stellen Hypothesen auf, die als Grundlage für eine Outcome‐Studie zu einer ähnlichen Intervention dienen könnten. 抄録: パキスタン農村部における新生児行動観察 (NBO) システム:実現可能性と妥当性の研究。概要 新生児行動観察 (NBO) システム™は、親が乳幼児の能力を認識できるようにし、その行動手がかりを知ることに焦点を当てた関係性に基づくツールであり、乳幼児−親の関係性における親の応答性と満足度を高めることを目的としている。このツールの実現可能性・妥当性研究では、米国在住の児童精神科医2名の遠隔指導のもと、パキスタンの農村部に住む乳幼児44名の小児科医の訪問健康診療にNBOを取り入れた。その後、臨床医が母親たちにNBOの体験についてアンケートを行ったところ、母親たちは高い満足度を示し、乳児の健康を高く評価し、乳児の行動の手がかりの理解が高まり、乳児への愛着をより強め、母親としての自信が高まったと報告された。これらの結果について、著者らは、母親たちの反応の文化的理由を探り、同様の介入の結果に関する研究を行うための仮説を立てている。 摘要: 新生儿行为观察 (NBO) 系统™ 是一种基于关系的工具, 旨在帮助父母识别婴儿的能力并学习其行为线索, 目的是增强父母在母婴关系中的反应能力和满意度。在这项可行性和可接受性研究中, 一名儿科临床医生在两名美国儿童精神科医生的远程指导下, 将NBO整合到巴基斯坦农村村庄的44次婴儿保健访视中。然后, 一名临床医生对母亲们进行了一项关于NBO体验的调查, 发现母亲们非常满意, 她们对婴儿的长处有了更多的了解, 对婴儿的行为线索有了更深刻的理解, 对婴儿有了更强烈的依恋, 作为母亲也有了更强的自信。在思考这些研究结果时, 本文作者探索了母亲反应的文化原因, 并提出假设, 为类似干预的临床实效研究提供信息。 ملخص: نظام الملاحظات السلوكية لحديثي الولادة (NBO) هو أداة قائمة على العلاقات تركز على مساعدة الآباء على التعرف على كفاءات أطفالهم وتعلم إشاراتهم السلوكية ، بهدف تعزيز استجابة الوالدين ورضاهم في العلاقة بين الرضيع والوالدين. في هذه الدراسة ، قام طبيب أطفال بدمج نظام الملاحظات السلوكية في 44 زيارة رعاية صحية للأطفال للرضع في قرى في المناطق الريفية في باكستان ، تحت إشراف طبيبين نفسيين للأطفال عن بعد في الولايات المتحدة. بعد ذلك ، أعطى الطبيب للأمهات استبيانًا حول تجربتهن مع نظام الملاحظات السلوكية ووجد أن الأمهات كن راضيات للغاية ، حيث أبلغن عن تقدير أكبر لنقاط القوة لدى أطفالهن ، وفهمًا أكبر للإشارات السلوكية لرضيعهن ، وتعلق أقوى برضيعهن ، وثقة أكبر بالنفس كأم. بالنظر في هذه النتائج ، يناقش الباحثون الأسباب الثقافية لاستجابات الأمهات ويضعون فرضيات لإثراء دراسة تدخلية مماثلة.